2008
DOI: 10.1007/s10544-008-9201-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of microdevices for studying anisotropic biaxial cyclic stretch on cells

Abstract: Mechanical effects on cells have received more and more attention in the studies of tissue engineering, cellular pathogenesis, and biomedical device design. Anisotropic biaxial cyclic stress, reminiscent of the in vivo cellular mechanical environment, may promise significant implications for biotechnology and human health. We have designed, fabricated and characterized a microdevice that imparts a variety of anisotropic biaxial cyclic strain gradients upon cells. The device is composed of an elastic membrane w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…While this model system was not able to incorporate stretch, we previously examined its effect on SMCs. Our previous work showed that the nuclear shape, proliferation, and cytoskeletal structure of SMCs were influenced by varied cyclic stretch mechanical loading (50). Thus the addition of cyclic stretch to the high pulsatility flow system could further contribute to SMC hypertrophy and hyperplasia and should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While this model system was not able to incorporate stretch, we previously examined its effect on SMCs. Our previous work showed that the nuclear shape, proliferation, and cytoskeletal structure of SMCs were influenced by varied cyclic stretch mechanical loading (50). Thus the addition of cyclic stretch to the high pulsatility flow system could further contribute to SMC hypertrophy and hyperplasia and should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that cells of several types (including mesenchymal cells) tend to upregulate proliferation in the presence of stretch (5,13,15,46,49). Also, fibroblasts have been shown to proliferate more rapidly in uniaxial than biaxial stretch, supporting the graded response result found here (15).…”
Section: Discussionsupporting
confidence: 69%
“…This concept can be scaled down to the microscale level, and MEMS devoted to the distention of cell substrates have been actuated by electrostatic actuators (Wu et al, 2005), fluids (Kim et al, 2007), and air pressure (Sim et al, 2007;Tan et al, 2008;Moraes et al, 2010).…”
Section: Simultaneous Stimulation With Cell Substrate Deformationmentioning
confidence: 99%